KONSTRUKSI KRITIK PERILAKU DISKRIMINATIF MASYARAKAT KOREA SELATAN TERHADAP PENYANDANG AUTISME - Harozim, Al Hammad (Universitas 17 Agustus 1945 Surabaya, 2025)
Most of the films and dramas produced by South Korea that tell about romance, but different from dramas that tell about the lives of people with autism spectrum. Drama “Extraordinary Attorney Woo” is one of the dramas with the theme of inspiration and touching in the life of a person with autism spectrum disorder who works at a large law firm. He has a high IQ of 164, an extraordinary memory, and a creative way of thinking but has a low EQ and poor social skills. Despite this, he is the smartest lawyer in South Korea with an autism spectrum disorder. This study aims to reveal the public perspective on autism spectrum disorder sufferers in the drama “Extraordinary Attorney Woo”. This research is motivated by the phenomenon of people with autism who often get discriminated against by their environment. Reality autism spectrum disorder described in the drama “Extraordinary Attorney Woo” is the focus of this research. The drama will be analyzed using John Fiske's semiotic theory. The results of this study indicate that in the drama